Fighting African Conflicts and Crimes: Which Governance Tools Matter? - Simplice A. Asongu; Oasis Kodila-Tedika (African Governance and Development Institute (AGDI), 2013)
Crimes and conflicts are seriously undermining African development. This article assesses the best governance tools in the fight against the scourges. The following findings are established. (1) Democracy, autocracy and voice & accountability have no significant negative correlations with crime. (2) The increasing relevance of government quality in the fight is as follows: regulation quality, government effectiveness, political stability, rule of law and corruption-control. (3) Corruption-control is the most effective mechanism in fighting crime (conflicts). The findings are significantly strong when controlling for age dependency, number of police (and security) officers, per capita economic prosperity, educational level and population density. Justifications for the edge of corruption-control (as the most effective governance tool) and policy implications are discussed.
Keywords: F52; K42; O17; O55; P16; 330; Security; Governance; Conflicts; Crime; Africa